The Organizational Bases of Ethical Work Climates - Victor, Bart; Cullen, John B. (Administrative Science Quarterly, 1988)
Using a modification of a recently developed measure of ethical climates, this paper presents evidence from a survey of 872 employees of four firms that ethical cork climates are both multidimensional and multidetermined. The study demonstrates that organizations have distinct types of ethical climates and that there is variance in the ethical within organizations by position, tenure, and workgroup membership. Five empirically derived dimensions of ethical climate are described: law and code, caring, instrumentalism, independence, and rules. Analyses of variance reveal significant differences in ethical climates both across and within firms. A theory of ethical climates is developed from organizational and economic theory to describe the determinants of ethical climates in organizations. In particular, the sociocultural environment, organizational form, and organization-specific history are identified as determinants of ethical climates in organizations. The implications of ethical climate for organizational theory are also discussed.